Effects of zeranol and A, D and E vitamins. I. On the performance of finishing crossbred steers. - Vieira, Paulo de Figueiredo; Sampaio, Alexandre Amstalden Moraes; de Oliveira, Mauro Dal Secco; Favoretto, Vanildo; Tosi, Hugo; Banzato, David Ariovaldo (Pesquisa Agropecuaria Brasileira, 2014)
Sixty-four crossbred animals Guzera x Holstein and Guzera x charolais, with average age of 21.4 ± 0,6 months and liveweight of 361.2 ± 11.6 kg were used in order to study the effocts of zeranol implant and A, D, and E vitamins minisiration, on the performance of finishing crassbred steers confined during the finishing period. The statistical design was in randamized blocks, in a factorial arrangement 2³, with two types of crossbreeding, two levels of vitamins (0 and 5.0 ml/animal) and two levels of anabolic agent (0 and 36.0 mg of zeranol/animal), with eight replications. The animal were fed with corn silage 'ad libitum', 4.0 kg of ground cron grain, both offered daily, in two meals, besides 1.0 kg of molasses and urea mixture (9:1), and 100 g of mineralized salt. The best liveweight gains (P < 0.01) were obtained with thee Guzera x Holstein crossbreds (1.29 kg/animal/day), compared to Guzera x Charolais crossbreds (1.16 kg/animal/day). The animals that received the anabolic agent showed gains of 1.27 kg/animal/day, higher than those that did not ceive it (1.18 kg/animal/day). The application of vitamins did not affect me weight gain of the animals, whose values were 1.22 and 1.22 kg/day to the animals with and without vitamins A, D, and E, respectively.